Men and house-work: Demographic variables, health, and satisfaction. - Sánchez-Herrero Arbide, Silvia; Sánchez-López, Mª del Pilar; Dresch, Virginia (Anales de Psicología / Annals of Psychology, 2009)
The purpose is to analyze men’s dedication to house-work and to child care, its relation to their health and satisfaction, and to determine the influence of sociodemographic variables (age, educational level, and type of family). The participants were 193 Spanish male workers (between 27 and 63 years of age), with children and diverse educational levels. The results show that men devote little time to house-work; age has an effect, but not the educational level or the number and age of the children. The fact that men do not perform house-work (which is done by the women) is related to higher satisfaction and better health. It seems that the role of men and women has not varied substantially with regard to previous generations.